Going Vague: Ambiguity and Avoidance in Online Political Messaging. (October 2019) - Chapp, Christopher; Roback, Paul; Johnson-Tesch, Kendra; Rossing, Adrian; Werner, Jack
Researchers have long investigated the conditions that promote the unambiguous communication of issues in political campaigns; however, previous research has been largely theoretic or has only tested ambiguous communication on a limited range of issues. We address these gaps, making three principal contributions. First, we provide an extensive empirical test of ambiguous communication, scoring every issue addressed on website "issues pages" from House candidates in 2014. Second, we accomplish this by using a supervised learning content analysis procedure that allows us to score a large volume of text based on a smaller subset of hand-coded text. This allows us to not only examine whether candidates comment on an issue but also the clarity of their message. Third, this article provides empirical support for how candidates' communication strategies are shaped not only by the candidates' personal characteristics but also the characteristics of the district. We find that district heterogeneity is an important predictor of ambiguous communication. Evidence also indicates that issue ownership and ideological extremity play a decisive role in the decision to "go vague."